Global wildlife trade and trafficking contribute to the world’s nonhuman primate conservation crisis - Garber, Paul A.; Estrada, Alejandro; Shanee, Sam; Svensson, Magdalena S.; Arregoitia, Luis Verde; Nijman, Vincent; Shanee, Noga; Gouveia, Sidney F.; Nekaris, K.A.I.; Chaudhary, Abhishek; Bicca-Marques, Júlio César; Hansen, Malene Fris (Frontiers in Conservation Science, 2024)
A growing global human population, habitat conversion, and the indiscriminate exploitation of natural resources have created unsustainable demands on nature, resulting in widespread biodiversity loss. Primates, which represent the third most specious Order of mammals, are facing an extinction crisis. Currently, 69% of primate species are listed by the IUCN as threatened (Vulnerable, Endangered, or Critically Endangered) and 94% have declining populations. Here, we examine two primary threats to primate population persistence, namely the commercialized hunting and capturing of wild primates and their body parts for food, traditional medicine, pets, and use in biomedical research. Both the legal wildlife trade and illegal wildlife trafficking represent multibillion-dollar industries that contribute to primate population decline, a reduction in genetic diversity, and local extirpation. Trade and trafficking also can lead to the emergence of infectious diseases, increasing biosecurity risks to humans. Between 2015 and 2021, CITES reported 337,511 live primates representing at least 99 species were legally traded, with 6.5% sourced directly from the wild. The recent indictment of Cambodian officials for allegedly laundering wild-caught long-tailed macaques into the U.S. by labelling them as captive-bred, highlights the need for greater transparency and accountability. Comprehensive data on the illegal trafficking of primates are extremely difficult to obtain. However, between 2009 and 2017, primates accounted for 20% of all seizures of illegally traded mammals in the air transport sector. International wildlife trafficking is dominated by criminal networks, corruption, and driven by the demands of wealthy consumers. In addition, the internet has expanded international opportunities to connect buyers and sellers of wild-caught primates and their body part. Despite explicit bans on selling endangered primates, social media sites continue to do so. Moreover, data on the global food security index (GFSI) indicate that as the international demand for wild live primates, their meat, and other body parts has continued to increase, the majority of people in primate range nations have remained food insecure. Given that almost 70% of primate species are negatively impacted by hunting and trapping, we offer a set of recommendations to reduce the trade and trafficking of wild primates.